Corporate Policy Peculiarities of Higher Professional Educational Institutions Necessitating Educational Space Modernization; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Loshchilova M. A. Marina Andreevna (2017, 2017)
Title screen